2015
DOI: 10.2174/0929867322666150114163051
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Interaction Between Mitochondrial Proteins and Amyloid-β Peptide and its Significance for the Progression and Treatment of Alzheimer’s Disease

Abstract: Abstract:The amyloid-β peptide (Aβ) has been associated with Alzheimer's disease (AD) for decades. The original amyloid cascade hypothesis declared that the insoluble extracellular plaques were responsible for Aβ toxicity. Later, this hypothesis has been updated and soluble intracellular Aβ forms and their effects within the cell have come into focus. Mitochondrial dysfunction plays an important role in the pathophysiology of AD. Aβ was detected inside mitochondria and several mitochondrial proteins were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 254 publications
(364 reference statements)
0
22
0
Order By: Relevance
“…Severe structural and functional abnormalities of the mitochondria were observed in the immediate vicinity of A β plaques [ 7 ]. Moreover, A β gradually accumulates within the mitochondria of both living mouse models of AD and human AD brain sections, and A β has been found to directly interact with several mitochondrial proteins, for example, cyclophilin D (CypD), amyloid- β binding alcohol (ABAD) dehydrogenase, and dynamin-related protein 1 (Drp1) [ 8 ]. These interactions impair the physiological functions of mitochondria, resulting in limited electron transfer, abnormal adenosine 5′-triphosphate (ATP) production, increased production of reactive oxygen species (ROS), and altered mitochondrial morphology and mobility in AD transgenic models [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe structural and functional abnormalities of the mitochondria were observed in the immediate vicinity of A β plaques [ 7 ]. Moreover, A β gradually accumulates within the mitochondria of both living mouse models of AD and human AD brain sections, and A β has been found to directly interact with several mitochondrial proteins, for example, cyclophilin D (CypD), amyloid- β binding alcohol (ABAD) dehydrogenase, and dynamin-related protein 1 (Drp1) [ 8 ]. These interactions impair the physiological functions of mitochondria, resulting in limited electron transfer, abnormal adenosine 5′-triphosphate (ATP) production, increased production of reactive oxygen species (ROS), and altered mitochondrial morphology and mobility in AD transgenic models [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an age-related loss of endogenous antioxidant defense mechanisms such as superoxide dismutase (Sod), heme oxygenase 1 (Hmox1), and γ -glutamyl cysteinyl synthetase (Gclm) accelerates oxidative stress in the brain. Similarly, during the aging process, amyloid beta peptides may enter mitochondria and disrupt mitochondrial function [ 6 ]. It has also been demonstrated that proteasomal activity decreases in the aging brain; thus, the cellular ability to degrade oxidized proteins may be impaired [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is directly associated with mitochondrial dysfunction being an early event in AD pathogenesis, as reflected in reduced metabolism, disruption of Ca 2ϩ homeostasis, increased free radical production, and lipid peroxidation (5)(6)(7)(8)(9). A␤ also affects mitochondrial respiration (10) and activates cytochrome c release, resulting in apoptosis (11).…”
mentioning
confidence: 99%